Mass drug administration of ivermectin and dihydroartemisinin–piperaquine against malaria in settings with high coverage of standard control interventions: a cluster-randomised controlled trial in The Gambia. Issue 4 (April 2022) - Dabira, Edgard D; Soumare, Harouna M; Conteh, Bakary; Ceesay, Fatima; Ndiath, Mamadou O; Bradley, John; Mohammed, Nuredin; Kandeh, Balla; Smit, Menno R; Slater, Hannah; Peeters Grietens, Koen; Broekhuizen, Henk; et al.
Summary: Background: Although the malaria burden has substantially decreased in sub-Saharan Africa, progress has stalled. We assessed whether mass administration of ivermectin (a mosquitocidal drug) and dihydroartemisinin–piperaquine (an antimalarial treatment) reduces malaria in The Gambia, an area with high coverage of standard control interventions. Methods: This open-label, cluster-randomised controlled trial was done in the Upper River region of eastern Gambia. Villages with a baseline Plasmodium falciparum prevalence of 7–46% (all ages) and separated from each other by at least 3 km to reduce vector spillover were selected. Inclusion criteria were age and anthropometry (for ivermectin, weight of ≥15 kg; for dihydroartemisinin–piperaquine, participants older than 6 months); willingness to comply with trial procedures; and written informed consent. Villages were randomised (1:1) to either the intervention (ivermectin [orally at 300–400 μg/kg per day for 3 consecutive days] and dihydroartemisinin–piperaquine [orally depending on bodyweight] plus standard control interventions) or the control group (standard control interventions) using computer-based randomisation. Laboratory staff were masked to the origin of samples. In the intervention group, three rounds of mass drug administration once per month with ivermectin and dihydroartemisinin–piperaquine were given during two malaria transmission seasons from Aug 27 to Oct 31, 2018, and from July 15 to Sept 30, 2019. Primary outcomes were malaria prevalence by qPCR at the end of the second intervention year in November 2019, and Anopheles gambiae (s l) parous rate, analysed in the intention-to-treat population. This trial is registered with ClinicalTrials.gov, NCT03576313 . Findings: Between Nov 20 and Dec 7, 2017, 47 villages were screened for eligibility in the study. 15 were excluded because the baseline malaria prevalence was less than 7% (figure 1 ). 32 villages were enrolled and randomised to either the intervention or control group (n=16 in each group). The study population was 10 638, of which 4939 (46%) participants were in intervention villages. Coverage for dihydroartemisinin–piperaquine was between 49·0% and 58·4% in 2018, and between 76·1% and 86·0% in 2019; for ivermectin, coverage was between 46·9% and 52·2% in 2018, and between 71·7% and 82·9% in 2019. In November 2019, malaria prevalence was 12·8% (324 of 2529) in the control group and 5·1% (140 of 2722) in the intervention group (odds ratio [OR] 0·30, 95% CI 0·16–0·59; p<0·001). A gambiae (s l) parous rate was 83·1% (552 of 664) in the control group and 81·7% (441 of 540) in the intervention group (0·90, 0·66–1·25; p=0·537). In 2019, adverse events were recorded in 386 (9·7%) of 3991 participants in round one, 201 (5·4%) of 3750 in round two, and 168 (4·5%) of 3752 in round three. None of the 11 serious adverse events were related to the intervention. Interpretation: The intervention was safe and well tolerated. In an area with high coverage of standard control interventions, mass drug administration of ivermectin and dihydroartemisinin–piperaquine significantly reduced malaria prevalence; however, no effect of ivermectin on vector parous rate was observed. Funding: Joint Global Health Trials Scheme. Translation: For the French translation of the abstract see Supplementary Materials section.